Driving Success Through Adaptive Performance in The Tech World - Frianto, Agus; Husain, Muhammad; Ramadani, Bima Yatna Anugerah; Anah, Lik (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
The development of information technology has had a significant impact on various aspects of human life. Adapting to changes and increasing one's knowledge is important to maintain the competitiveness and success of the company. The use of information technology also plays an important role in improving performance and productivity in the workplace. Knowledge sharing can help individuals to continuously update and improve their skills and improve work quality and efficiency. Crucial skills in the context of a constantly changing work environment, involve the ability of individuals to adjust their behavior and actions in response to changing situations and demands that arise in the work environment. This research uses positivism-based quantitative methods to test hypotheses by understanding the population and analyzing data quantitatively. The population is determined as individuals who are the subject of research, allowing researchers to make more accurate conclusions and meaningful recommendations. The sample used 116 students who took MBKM off campus. Investments in information technology and the development of a knowledge-sharing culture improve overall organizational performance. Information technology facilitates knowledge sharing between individuals, increasing adaptability to rapid changes in the work environment.